Lecturers And Students Perceptions Of Web-Based Learning With Simaster - Luthfatul Qibtiyah; Desta Fitriyani (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2023)
Indonesia has been designated as an area with PSBB (Large-Scale Social Restrictions) this is due to environmental conditions that are still spreading the COVID-19 virus. Thus causing a change in the method of organizing Learning and Teaching Activities (KBM), that is by changed the implementation of offline education to online education. It also occure Institute Dirosat Islamiyah Al-Amien (IDIA) Prenduan which uses information tecnology media and platform teaching-learning system, namely web-based learning with SIMASTER at IDIA Prenduan. In this research, the researcher used a qualitative approach with the type of phenomenological research. Data collection methods in this research used are interviews and documentation. The problem raised in this research is regarding the implementation of web-based learning with SIMASTER as various perceptions that lecturers and students describe about the implementation of web-based learning with SIMASTER and several opportunities and obstacles that occur in the implementation of SIMASTER-based lectures as well in the education Islamic study program at IDIA Prenduan. The learning process through SIMASTER uses a web-based learning system or digital platform. The opportunities of SIMASTER lectures always carried out, there are no empty schedules/classes, the lecture system becomes an information technology-based system and SIMASTER can be developed in hybrid lectures. The obstacles are lecturers who are not skilled in using SIMASTER and require more adequate internet network facilities.